IMPLEMENTASI LAYANAN BIMBINGAN KELOMPOK SEBAGAI UPAYA PENINGKATAN KESEHATAN MENTAL WARGA BINAAN LAPAS KELAS III RANGKASBITUNG - Mochamad Ilham Ramadhan; Arga Satrio Prabowo; Raudah Zaimah Dalimunthe; Angga Sugara Febriantiko (Jurnal Manajemen Pendidikan, 2026)
Correctional institutions represent high-risk environments for psychological disturbance, with inmates frequently experiencing complex mental health challenges particularly concerning family relations, self-acceptance, and social interaction. This study aims to implement and evaluate group guidance services utilizing problem-solving techniques within a Participatory Action Research (PAR) framework to enhance the mental well-being of adult early inmates at Lapas Kelas III Rangkasbitung. The study employed PAR design involving 50 inmates. Preliminary needs assessment using the Alat Ungkap Masalah (AUM) Umum Masyarakat instrument revealed dominant issues in family relations (13.33%), personal self (12.97%), and social relations (10.76%). Eight structured group guidance sessions were implemented, systematically integrating problem-solving stages from issue identification to collaborative action planning. Findings indicate that PAR-based group guidance significantly improved participants' self-awareness, interpersonal communication, emotional regulation, and problem-solving competencies. The participatory methodology effectively fostered active engagement, ownership of the change process, and real-time adaptation based on group dynamics. These findings validate integration of data-driven assessment, structured group techniques, and participatory frameworks as a sustainable strategy for psychological rehabilitation in correctional settings.